Evaluation of guggulsterone derivatives as novel kidney cell protective agents against cisplatin-induced nephrotoxicity - Lee, Dahae; Kim, Taejung; Kim, Ki Hyun; Ham, Jungyeob; Jang, Tae Su; Kang, Ki Sung; Lee, Jae Wook (Pergamon Press Ltd., 2017)
Guggulsterone derivatives were prepared using [3+2] click chemistry with aryl and alkyl acetylene. The series of derivatives were evaluated for their cellular protective effects on cisplatin-treated cultured LLC-PK1 kidney epithelial cells. Among the guggulsterone-triazole derivatives, compound 6g, which contains a hydroxyl methyl group, was the most active of all the derivatives. In an additional study, we determined that inhibition of the mitogen-activated protein kinase/caspase-3 signaling cascade by 6g mediates its protective effects against cytotoxicity in cultured LLC-PK1 cells. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: NF-KAPPA-B; OXIDATIVE STRESS; NATURAL PRODUCT; IN-VITRO; ANTAGONIST; DISEASE; TRANSCRIPTION; CONSTITUENT; ACTIVATION; GINSENG